2014
DOI: 10.7762/cnr.2014.3.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and the Risk of Thyroid Cancer: A Review

Abstract: In the past few decades, the incidence of thyroid cancer has rapidly increased worldwide. Thyroid cancer incidence is relatively high in regions where the population's daily iodine intake is insufficient. While low dietary iodine has been considered as a risk factor for thyroid cancer development, previous studies found controversial results across different food types. Among different ethnic groups, dietary factors are influenced by various dietary patterns, eating habits, life-styles, nutrition, and other en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 47 publications
(100 reference statements)
2
53
1
1
Order By: Relevance
“…In this cohort study, we observed no association between differentiated TC risk and the consumption of cruciferous vegetables. Similar results were observed in two meta‐analyses and one pooled‐analysis . However, in the most recent meta‐analysis, a positive association was pointed out, after excluding studies evaluating only one type of cruciferous vegetables and hospital‐based case‐control studies .…”
Section: Discussionsupporting
confidence: 73%
“…In this cohort study, we observed no association between differentiated TC risk and the consumption of cruciferous vegetables. Similar results were observed in two meta‐analyses and one pooled‐analysis . However, in the most recent meta‐analysis, a positive association was pointed out, after excluding studies evaluating only one type of cruciferous vegetables and hospital‐based case‐control studies .…”
Section: Discussionsupporting
confidence: 73%
“…5,6 Although thyroid nodules and well-differentiated TC are more often detected in women than in men, the associations with individual reproductive and menstrual factors and female hormone use are, if anything, weak. 7 Dietary factors, including some food groups (fish, shellfish, meat, starchy foods, fruits and vegetables), 8,9 macronutrients, 10 vitamins, microelements (iodine, nitrate and nitrites), 8,[11][12][13] glycemic index (GI) and load (GL) 14 and local traditional dietary patterns (Polynesian dietary pattern) 15,16 have been studied in respect to TC risk. However, findings were mainly based on case-control studies and are inconclusive.…”
Section: And High Bodymentioning
confidence: 99%
“…However, findings were mainly based on case-control studies and are inconclusive. 8,9 Chronic iodine deficiency is the only dietary recognized risk factor for goiter and follicular TC. 8 The aim of this study was to evaluate prospectively the relationships among total energy intake, macronutrient composition (including sugar, starch, fiber and fats), GI and GL and the risk of developing differentiated TC in a large European cohort: the European Prospective Investigation into Cancer and Nutrition (EPIC) study.…”
Section: And High Bodymentioning
confidence: 99%
“…In 2001, Zhu [70] reported a case of thyroid neoplasm following marine algae in a breast cancer. From epidemiologic studies in Korean population, high intake of iodine from marine products may increase thyroid cancer risk,particularly in women [71,72].Accumulated data, seaweed accounts for about 80% of Japanase people's iodine intake, seaweed consumption was clearly associated with an increased risk of papillary carcinoma (PTC)in postmenopausal women [73]. introduced in 1985,the thyroid cancer incidence increased in females from 1.56/100,000 during 1978-1985 to 8.23/100,000 in period from 1984 to 2001,the PTF:FTC increased from 2.3 to 11.5 [85].Italy had one of the highest incidence rates for thyroid cancer,nearly 20/100,000 women in 2007,the frequency of thyroid cancer in females with cold nodules was 5.3% in the iodine sufficient area (mean UIC 114 µg/l) and 2.7% in the iodine deficient area (mean UIC < 50 µg/l) [86].The highest incidence rates for thyroid cancer are Japan, where iodine intake is high [22].…”
Section: Iodine Induced Hyperthyroidism (Iit)and Thyrotoxicosis (Iit)mentioning
confidence: 99%
“…These include low iodine diets, radioactive iodine and natural goitrogens. Dietary iodine intake act as a potential relavance risk factor of thyroid cancer [21,[71][72][73][74][75][76].Elevated incidence and mortality rate of thyroid cancer have been found in areas where iodione intake is high(Howaii, Iceland) [76][77][78].In South India, among 300 patients with goiter and 100 euthyroid health non-goitrous volunteers, iodine-induced hyperthyroidism or IIT (34%)and thyroid cancer (15%)have been observed after continued supplement of edible salt fortified with excess iodine [79]. In China, using comparative analysis of 4679 post-operative patients with universal salt iodization (USI)during 1994-2008 and 3325 post-operative patients without USI during 1979-1993,the incidence ratio of thyroid carcinoma after USI was 5.6% (308/4679)compared to 2.9% (95/3325) in patients without USI,32.7% (1530)of thyroid adenoma after USI compared to 20% (665)before USI, and 4.5% (212) of toxic goiter after USI compared to 2.7% (95) before USI [80].According to 1101 thyroid malignant tumors confirmed by pathological specimens, constitional ratio of PTC (70.17%)increased obviously after USI compared with the results (55.84%)before USI whereas the proportion of FTC (11.05%)decreased accordingly after USI compared with the results (24.58%) before USI [81].…”
Section: Dietary Iodine Intake and The Prevalence Of Papillary Carcinmentioning
confidence: 99%